Energy Conservation Potentials in University of Maiduguri: Case Study of Shettima Ali Monguno Hostel. - Malut, A. M.; El-Jummah, A. M.; Muhammad, A. B. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
This paper presents the result of investigating the energy conservation potentials conducted at Shettima Ali Monguno (SAM) Sudents’ Hostel of University of Maiduguri. The aim of the study was to ascertain the energy consumption pattern and the amount of energy consumed, spot areas of waste and find measures to curb such waste. A walk-through audit and investigation through questionnaire and oral interviews were used to gather required data. Microsoft Excel software were used to analyse the data. The results show that fan element ranked top in energy consuming loads having 86 %, followed by lighting 73 %, resistant coil 25%, pressing iron 18% and electric hot plate 13%. And the aspect of cooking kerosene ranked up to the most used energy followed by charcoal. The annual energy and cost savings for replacement of conventional resistance electric regulator fans with electronic regulator fans is about 17MWh and N 1.1Million and that one for replacing incandescent light bulb is 13MWh and N0.9Million.The study recommends that Energy audit should be conducted for other parts of the institution, awareness on energy saving habits and their benefits should be created.